Implementation of Learning Supervision in Improving Educator Performance: Case Study at Madrasah Aliyah Banat Kudus, Central Java, Indonesia - Siti Nafisatun (Tarbiyah Departement collaboration with AMCA, 2022)
This study aims to describe the learning supervision activities carried out at Madrasah 'Aliyah Nahdlatul 'Ulama (MA NU) Banat. The research method used is descriptive qualitative, with the resource persons being the head of the madrasa and the teacher. In addition, researchers also made direct observations to explore data related to supervision carried out at MA NU Banat. The results of this study indicate that the implementation of supervision at MA NU Banat is carried out in 2 (two) models, namely academic supervision and clinical supervision. The steps in clinical supervision are divided into planning supervision, implementation of supervision and evaluation of supervision. The implementation of supervision is carried out in 4 (four) stages, namely interviews with supervisees, supervisees prepare and conduct clinical supervision, supervisors make observations and make assessment notes, feedback from the implementation of clinical supervision.